Anti-Militarism in Joseph Heller’s Catch-22 - JABBAR, SABAH SALIM (Al-Adab Journal, 2015)
The paper attempts to address Joseph Heller in his novel, Catch-22 (1961). An examination of the content of the novel in relation to antimilitaristic concepts is a major focus of the paper. The paper depicts various characters in the novel and tries to show how they reflect antimilitarism. The effects of particular behaviors and the major events that take place in the Air Force are discussed in the paper. The story mainly revolves around some airmen who were combatants in World War II. The events discussed in the paper clearly highlight the sentiments held by antimilitarists on war issues. The plot of the novel is sequential and the description of events is comic. The characters represent various characteristics that can be used to develop a plot on antimilitarism. The paper bases its literature of the aspects of the military that necessitate and justify the rise and development of antimilitarism. Socialism is a notable aspect of antimilitarism while militarism seems to conform to capitalism. From an antimilitaristic perspective, capitalism is characterized by a type of bureaucracy that demoralizes soldiers and promotes individuality within the military. Catch-22 deals with all the militaristic and antimilitaristic factors and events that lead to the same aspects.